Materiais carbonáceos sustentáveis em benefício da remediação ambiental e armazenamento de energia - Vieira, Laís Helena e Sousa (2023)
Carbonaceous materials (CMs) such as hydrochar and carbonaceous nanocomposite were prepared by hydrothermal carbonization (HTC) followed by thermochemical activation from different carbon sources: glucose, cellulose and sugarcane bagasse (in natura biomass). The CMs were studied in terms of their physicochemical properties for application in environmental remediation and energy storage. Magnetic carbonaceous nanocomposites (MCN) were prepared by HTC of glucose in the presence of Fe3+, followed by thermochemical activation with KOH to increase the specific surface area, porosity and transformation into magnetic phase. The CMs were obtained from hydrothermal carbonization of cellulose and sugarcane bagasse with and without Fe3+ and thermochemically activated with KOH. Regardless of the carbon source, structural similarities were observed regarding the encapsulation of iron oxide in the carbonaceous matrix, the predominant presence of the magnetite phase after activation, and high specific surface area (> 700 m2·g-1) and microporosity of the nanocomposites. Adsorption tests with the cationic dye methylene blue (MB) were carried out to evaluate the multifunctionality of magnetic nanocomposites (adsorption followed by magnetic separation). The sample with the best performance had a removal capacity of 570 mg·g-1 at room temperature. All samples obtained from sugarcane bagasse were processed into thin films via the liquid-liquid interfacial route (LLIR). This methodology ensured the formation of transparent and thin films with a thickness ranging from 18 and 157 nm. The thin films obtained from sugarcane bagasse after activation presented the highest values of volumetric specific capacitance, (Cv), 442 and 83 F·cm-3. With the MCNs obtained from glucose, it was possible to present a model for obtaining carbonaceous materials from different biomasses (cellulose and sugarcane bagasse). Thus, based on the same preparation methodology, it was possible to obtain multifunctional materials as an alternative for the development of electrodes for energy storage, as well as magnetic adsorbents.